The Predicting Effects of Self-Efficacy, Self-Esteem and Prior Travel Experience on Sociocultural Adaptation Among International Students - Mehari, Desbele Tekie; Gebretinsae, Dawit Yikealo; Tesfamariam, Aster Habte (Journal of International Students, 2020)
Personal and situational factors contribute to international students’ sociocultural adjustment in a host society. Thus this study attempts to determine the roles of self-efficacy, self-esteem, and previous travel experience on sociocultural adjustment. The sample for this study constituted 328 undergraduate and postgraduate international students, studying in three Chinese universities. Participants completed a set of tests measuring their sociocultural adjustment, self-efficacy and self-esteem, as well as answered demographic questions. Hierarchical multiple regression and a PROCESS macro were used to analyze the data. Results revealed that prior travel experience, self-efficacy, and self-esteem significantly predicted sociocultural adaptation. In particular, self-esteem partially mediated the relationship between self-efficacy and sociocultural adaptation. Limitations and future study directions and implications for the findings are discussed.